Chinese Aesthetics of Situational Language Variety: A Study of 李薇 Character Studies in Drama 聊聊日常 (New Life Begins) 2022 - Dewi, Endah Putri; Nastiti, Nawang Putri; Suryana, Wahyu; Mintowati, Maria; Adhimas, Yogi Bagus (Confucius Institute Universitas Sebelas Maret, 2024)
In social life, communication is needed to be able to interact with each other using various ways, one of which is by speaking using existing languages. In language activities, there is a language phenomenon, namely the variety of languages according to the situation. Researchers decided to examine the drama 聊聊日常 (New Life Begins) (2022) because there are many data found on the variety of languages according to the situation used by the character 李薇 Lǐ Wēi. In this study, this author analyzes how the various forms of language used by 李薇 Lǐ Wēi characters according to the situation that is happening in the drama 聊聊日常 (New Life Begins) using the theory of Martin Joos (1967). Research data were obtained from various dialogues of 李薇 Lǐ Wēi characters with other characters contained in the drama 聊聊日常 (New Life Begins) with a descriptive qualitative approach. The results of the analysis showed that in episodes one to five of the drama 聊聊日常 (New Life Begins) Lǐ Wēi's character used all kinds of language according to the situation based on the level of formality according to Martin Joos (1967), namely frozen variety, official variety (formal), business variety (consultative), casual variety (casual), and familiar variety (intimate). However, it was found that Lǐ Wēi characters mostly use casual varieties.